COMBINATION DESIGN OF KNOWLEDGE DIMENSIONS AND THINKING PROCESS LEVELS ON PARABOLIC MOTION LEARNING DEVICES FOR PHYSICS LEARNING IN PEKANBARU CITY HIGH SCHOOL - Jeremia Vincensius; Amali Putra; - Murtiani; - Hidayati (Universitas Negeri Padang, 2022)
The 2013 curriculum for high school physics lessons mandates teachers to change learning patterns that are